الرؤى و الأفكار حول - مفاهيم و طرق تعليمية اللغة العربية في أوزبكستان - Hashem Esmael Hammam Ali; Ahmed Mahmoud Ahmed Mahmoud (“ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI” MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2024)
These visions and ideas appeared in some European countries at the beginning of the fifties in different forms due to their association with specializations consistent with their orientations. In some European countries, such as: France, Canada, Italy, and Switzerland, they were linked to psychology and psycholinguistics. Educational education is one of the main branches of applied linguistics, and it came because of developments in the curricula. Hence, education methods have become present in a continuous and evolving context due to the multiplicity of language fields applied.